Nipple-Sparing Mastectomy and Prepectoral Implant/Acellular Dermal Matrix Wrap Reconstruction in Large Ptotic Breasts. Issue 7 (July 2019) - Khalil, Haitham H.; Malahias, Marco N.; Youssif, Sherif; Ashour, Tarek; Rhobaye, Saif; Faroq, Tahir
Abstract : Summary: Nipple-sparing mastectomy (NSM) with simultaneous prepectoral direct to implant reconstruction and acellular dermal matrix (ADM) is increasingly offered to patients opting for prophylactic or therapeutic mastectomies. The recent introduction of prepectoral implant/ADM in the armamentarium of breast reconstruction has proven to reduce pain and animation deformity. Despite this promising method, patients with macromastia and ptotic breasts remain a challenging group to treat. More often they would require secondary corrective procedures and can experience high failure rate and unsatisfactory outcomes. The authors present their experience in utilizing a bipedicled nipple-areola complex dermal flap through Wise pattern to achieve a successful NSM with prepectoral implant/ADM (Braxon) wrap (IBW) as a single stage in patients with large ptotic breasts. Patients seeking NSM with large ptotic breasts were included in the study in the period between 2016 and 2018. They were offered a single-stage Wise pattern NSM and immediate prepectoral IBW breast reconstruction. The technique and outcomes were recorded. Sixteen reconstructions were performed in 8 women with a median age of 32 years (range, 27–50 years) and a median body mass index of 32 kg/m 2 (range, 29–39 kg/m 2 ). The resected breasts weight ranged from 750 to 1, 600 g (median, 890 g). All procedures were completed successfully with no nipple-areola complex necrosis or failure experienced during the follow-up period (range, 3–24 months) with all patients reported excellent satisfaction. The authors' results demonstrate that this technique could be safely planned for NSM in large ptotic breasts with excellent durable outcomes. Abstract : Supplemental Digital Content is available in the text.